Renal zoomed EPI-DWI with spatially-selective radiofrequency excitation pulses in two dimensions - He, Yong-Lan; Hausmann, Daniel; Attenberger, Ulrike; Schönberg, Stefan; Riffel, Philipp (European journal of radiology, 2016)
Purpose - To evaluate the feasibility and clinical robustness of zoomed diffusion-weighted echo planar imaging (z-EPI) relative to conventional single-shot EPI (c-EPI) for DWI of the kidneys. - Materials and methods - This retrospective study was approved by the institutional research ethics board. 66 patients (median age 58.5 years±13.4, range 23-83 years, 45 men, 21 women) undergoing 3T (Magnetom Skyra®, Siemens Healthcare, Erlangen, Germany) using a dynamic parallel transmit array (TimTX TrueShape, Siemens Healthcare, Erlangen, Germany) for renal MRI were included in this study. Both c-EPI and z-EPI images were obtained. For z-EPI, a two-dimensional spatially-selective radiofrequency (RF) pulse was applied for echo planar imaging with the FOV reduced by a factor of 3. Two radiologists, blinded to clinical data and scan parameters evaluated the images with respect to their diagnostic confidence, overall preference, overall image quality, delineation of the kidney, spatial distortion, and image blur. Sequences were compared using a paired Wilcoxon test. ADC values for the upper pole, mid-zone, lower pole of the normal kidneys were compared between sequences as well as ADC values for renal lesions, using a paired t-test. - Results - With z-EPI, the kidney was significantly better delineated with sharper boundaries, less image blur and distortion, and overall better image quality relative to c-EPI (all p<0.001). The z-EPI technique led to greater diagnostic confidence than c-EPI (p=0.020). z-EPI was preferred to c-EPI in 60 cases (90.9%, 60/66). No statistically significant differences in the ADC values of renal parenchyma or of renal lesions were observed between the two sequences (all p>0.05). - Conclusion - Image quality, distortion, and susceptibility artifacts might be improved by using z-EPI rather than c-EPI for DWI of the kidney.